Pengaruh Pola Dan Jarak Elektroda Pada Proses Elektrokoagulasi Limbah Cair Industri Tahu - Aditya Nugraha; Idral Amri; Irdoni HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Tofu industry in Lirik produce 0.9 m3 liquid waste in a day, and immeditely disposed without processing. There are two parameters in liquid waste that exceed standard value in Permen LH No.5 2014, which is TSS and pH. Electrocoagulation method used to decrease TSS and increase pH of waste. By varying pattern and range of electrode, obtained results: (1) The best electrode pattern was 2 cathode – 2 anode with TSS removal efficiency was 75%, and increase pH from 3.9 to 6.8. (2) Range of electrode 1.5 and 2.0 cm resulted the greatest TSS removal efficiency were 75% and 76.39%, but in range 2.0 cm increase of pH was only up to 6.1, while in range 1.5 cm it increased to 6.8.Keywords : electrocoagulation, TSS , pH